CT-Informed Skull Osteology of Palaeolagus haydeni (Mammalia: Lagomorpha) and Its Bearing on the Reconstruction of the Early Lagomorph Body Plan - Wolniewicz, Andrzej S.; Fostowicz-Frelik, Łucja (Frontiers in Ecology and Evolution, 2021)
Lagomorpha is a clade of herbivorous mammals nested within Euarchontoglires, one of the major placental groups represented today. It comprises two extant families with markedly different body plans: the long-eared and long-limbed Leporidae (hares and rabbits) and the short-eared and short-limbed Ochotonidae (pikas). These two lagomorph lineages diverged probably during the latest Eocene/early Oligocene, but it is unclear whether the last common ancestor of crown lagomorphs was more leporid- or more ochotonid-like in morphology. Palaeolagus, an early lagomorph dominant in western North America from the late Eocene to Oligocene is of particular importance for addressing this controversy. Here, we present new and comprehensive data on the cranial anatomy of Palaeolagus haydeni, the type species for the genus, based on micro-computed tomography (μCT). Our μCT data allow us to confirm, revise and score for the very first time the states of several leporid-like and ochotonid-like characters in the skull of Palaeolagus. This mixed cranial architecture differentiates Palaeolagus from the crown groups of Lagomorpha and supports its phylogenetic status as a stem taxon.